2012
DOI: 10.1002/mus.23508
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective study of complications of therapeutic plasma exchange in myasthenia

Abstract: PV access for TPE can be used successfully in most MG patients and may reduce morbidity of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
3
29
1
Order By: Relevance
“…Nevertheless, several studies describe increased complications rates with central lines in this setting [ 41 , 42 ]. As a less invasive alternative, successful TPE with peripheral venous access was demonstrated even in neurology patients [ 42 , 43 ]. Central lines offer a continuous high blood flow rate and a straight workflow in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies describe increased complications rates with central lines in this setting [ 41 , 42 ]. As a less invasive alternative, successful TPE with peripheral venous access was demonstrated even in neurology patients [ 42 , 43 ]. Central lines offer a continuous high blood flow rate and a straight workflow in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…It is more invasive, more labor-intensive and more expensive than ivIG (97). PE should be performed via peripheral venous access, where feasible, but central catheters may be necessary in some which pose additional risks of an infection source if mishandled or if left in situ for too long (98). The same dose of ivIG could be administered over a shorter period for example 2-3 days if tolerated by the patient.…”
Section: The Mg Patient In Crisismentioning
confidence: 99%
“…Venous access for plasma exchange can be achieved by central venous catheters or peripheral veins, and the preferred method varies among providers. Very recently, one retrospective study showed that peripheral veins access can be used successfully in most myasthenic patients and reduces the risk of serious and even lethal complications of the procedure .…”
Section: Introductionmentioning
confidence: 99%